Gas Sensors Based on U-shaped Graphene Nanoribbons: A first-principles Study - Nguyen, Tien Cuong (H. : ĐHQGHN, 2020)
In this paper, I present first-principle calculations which are performed by using combination of DFT and NEGF methods to investigate the adsorption of CO2 and NH3 molecules on straight and U-shaped GNRs junctions. The density of state, molecular orbital, adsorption energy, transmission spectrum, and current-voltage characteristics were analyzed. It is found that the adsorption of CO2 and NH3 on straight GNRs at the dangling bond edges exhibit chemical interaction behavior with high adsorption energy. Besides, for U-shaped ZGRNs without adsorption, the states around Fermi level are quasi-bound states localized at the zigzag edges. The electrons at these localized states are almost confined and do not contribute on conductance. However, for U-shaped GRNs with CO2 and NH3 adsorbed on DB armchair edge defects, these states become delocalized on whole of the U-shaped junction. The current-voltage characteristics show that the sensitivity and selectivity of the U-shaped GNRs gas sensors are significantly improved in comparison with the pristine GNR ones.